2015
DOI: 10.1055/s-0035-1552936
|View full text |Cite
|
Sign up to set email alerts
|

Regional Brain Biometrics at Term-Equivalent Age and Developmental Outcome in Extremely Low-Birth-Weight Infants

Abstract: TE-MRI biometrics reflecting impaired deep gray matter, callosal, and cerebellar size is associated with worse early childhood cognitive and motor outcomes. DGMA may be the most robust single biometric measure to predict adverse developmental outcome in preterm survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The large proportion of the population exceeding this cut-off value limits the utility BPW as a predictor for adverse outcome. Additionally, results for BPW are inconsistent [5,7,19]. Contrary to the aforementioned study, Melbourne et al [19] did not observe any association between BPW and developmental outcome in a small cohort of very preterm infants, including also those with brain injury.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The large proportion of the population exceeding this cut-off value limits the utility BPW as a predictor for adverse outcome. Additionally, results for BPW are inconsistent [5,7,19]. Contrary to the aforementioned study, Melbourne et al [19] did not observe any association between BPW and developmental outcome in a small cohort of very preterm infants, including also those with brain injury.…”
Section: Discussionmentioning
confidence: 85%
“…Additionally, results for BPW are inconsistent [5,7,19]. Contrary to the aforementioned study, Melbourne et al [19] did not observe any association between BPW and developmental outcome in a small cohort of very preterm infants, including also those with brain injury. Dewan et al [7] recently stated that a small BPW is not a risk factor for neurodevelopmental impairment in a cohort of very preterm infants without high-grade injury.…”
Section: Discussionmentioning
confidence: 85%
“…17 At TEA, transcerebellar diameter was associated with fidgety general movements at 3-month corrected age (CA), 18 poorer cognitive outcomes at 12-month CA, 19 and poorer motor and cognitive outcomes at 2-year CA. 20 Reduced deep gray matter area at TEA was associated with poorer motor and cognitive outcomes, 19 and an increased interhemispheric distance independently predicted poorer cognitive development at 2-year CA. 3 Reduced biparietal width at TEA predicted both motor and cognitive outcomes at 2-year CA in infants born very preterm.…”
mentioning
confidence: 99%
“…Some authors found that preterm born infants have a higher prevalence of head shape abnormalities such as elongated head shape (dolichocephaly) [48]. Additionally, regional biometric differences reflecting impaired cerebellar size or deviating head diameters were reported in children [49] and adults [28] born preterm and may be associated with cognitive and motor outcomes [49].…”
Section: Discussionmentioning
confidence: 99%